2010
DOI: 10.1103/physrevd.81.094019
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic transverse parton momenta in deeply inelastic reactions

Abstract: Intrinsic transverse parton momenta pT play an important role in the understanding of azimuthal/spin asymmetries in semi-inclusive deep-inelastic scattering (SIDIS) and the Drell-Yan process (DY). We review and update what is presently known about pT from these processes. In particular, we address the question to which extent data support the popular Gauss model for the pT -distributions. We find that the Gauss model works very well, and observe that the intrinsic transverse momenta in SIDIS and DY are compati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
184
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(202 citation statements)
references
References 176 publications
18
184
0
Order By: Relevance
“…A recent study [110] analyzed these data in combination with the CLAS data [111], and concluded that in the kinematics similar to the CLAS data, the Hall C data could be relatively well described by a Gaussian model with average transverse momentum width of 0.24 (GeV/c) 2 . The good description of the π ± cross sections from different targets was argued to indicate that the assumption of flavor-independent Gaussian width for both the transverse widths of quark and fragmentation functions was reasonable, in the valence-x region for z=0.…”
Section: E Nuclear Al/d Ratiosmentioning
confidence: 99%
“…A recent study [110] analyzed these data in combination with the CLAS data [111], and concluded that in the kinematics similar to the CLAS data, the Hall C data could be relatively well described by a Gaussian model with average transverse momentum width of 0.24 (GeV/c) 2 . The good description of the π ± cross sections from different targets was argued to indicate that the assumption of flavor-independent Gaussian width for both the transverse widths of quark and fragmentation functions was reasonable, in the valence-x region for z=0.…”
Section: E Nuclear Al/d Ratiosmentioning
confidence: 99%
“…ref. [50] for a study dedicated to this issue). The interpolation of a Gaussian with the small-b matching eqs.…”
Section: Jhep03(2017)002mentioning
confidence: 99%
“…A linear dependence on s has been also claimed for DY and SIDIS in Ref. [5]. However the linearity is very rough and approximate.…”
Section: Gaussian Modelsmentioning
confidence: 86%
“…27 but with the parameters of Ref. [5], setting the initial scale, Q 0 , as the average Q of the HERMES experiment. However, despite these modifications, the description of the HERMES experiment (which is the input for the evolution) is very bad, see Fig.1 of Ref.…”
Section: Tmd/css Phenomenologymentioning
confidence: 99%